UK Experience of an Alternative ATO Dosing Regimen in APL - Russell, Nigel; Dillon, Richard (Frontiers in Oncology, 2020)
The introduction of all-trans retinoic acid (ATRA), and more recently of arsenic trioxide (ATO) in the treatment of Acute Promyelocytic Leukaemia (APL), has been instrumental in achieving the high cure rates recently reported. For the majority of patients, it is now possible to successfully treat this disease “chemo-free” without the use of cytotoxic chemotherapy as reflected in current clinical guidelines. The Sanz risk score developed by the GIMEMA and PETHEMA groups categorizes patients into three risk groups—low, intermediate, and high and correlates with relapse-free survival (RFS). Low- and intermediate-risk APL are now often considered together as ‘standard-risk’ defined by a white blood cell count (WBC) of less than 10 x 109/L. High-risk APL has a WBC greater than 10 x 109/L. In the UK our approach for patients with standard risk APL is to treat with ATRA and ATO without the use of cytotoxic chemotherapy. This approach is based on results from two large randomized clinical trials. The GIMEMA APL0406 trial showed an overall survival advantage compared to anthracycline-based chemotherapy plus ATRA. The UK NCRI AML17 trial which used an attenuated dose of ATO demonstrated a significant reduction in relapse and improved relapse-free survival. In the UK, the National Institute for Clinical Excellence approved both ATO plus ATRA regimens for re-imbursement for standard risk Acute Promyelocytic Leukaemia (APL). We use the AML17 schedule in standard-risk patients upfront and also in patients with relapsed Acute Promyelocytic Leukaemia (APL) previously treated with chemotherapy or in those with molecular persistence. The treatment of high-risk Acute Promyelocytic Leukaemia (APL) remains an area of contention as ATO is not approved for this indication. These patients have a greater risk of complications during remission induction with ATO including differentiation syndrome. The optimal approach is to incorporate chemotherapy early into the treatment schedule with either Gemtuzumab Ozogamicin (GO) as in the high-risk arm of the NCRI AML17 trial and MD Anderson Cancer Centre studies or Idarubicin as in the Australian APML4 study.